Analisis Jam Kerja Dan Waktu Lembur Pada Perusahaan Manufaktur Kota BATAM - Alden Nelson; Adeline Oktalia; Emilya; Lia Willyanto; Monica Ella (STEKOM PRESS, 2023)
Provision of good working hours in accordance with standards must be maintained by businesses to fulfill all their goals, including the Indonesian manufacturing industry. The manufacturing industry in Indonesia must prioritize work standards, because these factors greatly affect a company's ability to achieve its goals. The purpose of this study was to determine the effect of working hours and overtime on resource management with industrial relations, to analyze working hours to attract employees and to analyze the calculation of employee wages. The author uses a qualitative descriptive method in this study. The result of this research is that everyone involved in industrial relations must understand the rules of the game and other regulations that apply in Indonesia. In terms of working hours or overtime policies, developing the quality of human resources, absenteeism and leave policies, and salary increases that are in accordance with industry standards, can improve employee welfare and productivity and maintain competitiveness in a company.